2023
DOI: 10.1111/jora.12880
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between friends on service, activism, and awareness of inequities in an adolescent social network

Abstract: This brief report characterizes the tendency of adolescent friends to be similar on civic behaviors and critical consciousness. Using two waves of network data from a high school that serves primarily low‐income Latiné youth (2019, N = 519; 2020, N = 521), the present study examined homophily on service, activism, and awareness of inequities. The results of Exponential Random Graph Models indicated that adolescents tended to be friends with peers who had similar service behavior and awareness of inequities, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Although friends' critical consciousness may contribute positively to mental health, robust developmental research on peer socialization has shown that youth who differ from their peers may experience pressure to conform or cultivate friendships with similar peers [48,49]. Youth tend to be similar to their friends (that is, they tend to exhibit "homophily" in friend groups) on political orientation, civic behavior, and critical reflection [50][51][52]. Over time, adolescents may influence each other to become more similar in critical consciousness through peer pressure, modeling, mentorship, the internalization of social norms, or the expression of shared identity.…”
Section: Friendship Network and Critical Consciousnessmentioning
confidence: 99%
“…Although friends' critical consciousness may contribute positively to mental health, robust developmental research on peer socialization has shown that youth who differ from their peers may experience pressure to conform or cultivate friendships with similar peers [48,49]. Youth tend to be similar to their friends (that is, they tend to exhibit "homophily" in friend groups) on political orientation, civic behavior, and critical reflection [50][51][52]. Over time, adolescents may influence each other to become more similar in critical consciousness through peer pressure, modeling, mentorship, the internalization of social norms, or the expression of shared identity.…”
Section: Friendship Network and Critical Consciousnessmentioning
confidence: 99%